Optimization of the extraction methods and evaluation of the hypoglycemic effect of Adhatoda Zeylanica extracts on artificially induced diabetic mice - Md Fahim Ahmed; Khalid Hasan Raby; Nishat Tasnim; Md Tariful Islam; Mahbub Chowdhury; Zarin Tasnim Juthi; Md Ashik Mia; Lubna Jahan; A.K.M. Zakir Hossain; Shoeb Ahmed (Heliyon)
Synthetic antidiabetic drugs are often associated with various adverse side effects, including hypoglycemia, nausea, gastrointestinal disturbances, headaches, and even liver damage. In contrast, plant-derived natural antidiabetic bioactive compounds typically exhibit lower toxicity and fewer side effects and have been reported to aid effectively in diabetes management. These plant extracts regulate diabetes by restoring pancreatic function, enhancing insulin secretion, inhibiting intestinal glucose absorption, and facilitating insulin dependent metabolism. This study explored four extraction methods, including reflux distillation (RD), ultrasound assisted extraction (UAE), microwave assisted extraction (MAE), and enzyme assisted extraction (EAE) to optimize the yield of crude leaf extract and vasicine from Adhatoda zeylanica. RD produced the highest crude extract yield (98.29 g/kg of dried leaf), while MAE was the most effective for vasicine extraction, yielding 2.44 g vasicine per kg dried leaf. High Performance Liquid Chromatography (HPLC) with a diode array detector (DAD) was used to identify and quantify vasicine, a quinazoline alkaloid with known antidiabetic properties. The hypoglycemic effects of leaf extracts were evaluated in alloxan-induced diabetic mice, and the effect of A. zeylanica extract was compared to the extracts of Centella asiatica, Allamanda cathartica, and the standard drug metformin. At a dose of 400 mg/kg body weight (BW), methanolic leaf extracts of A. zeylanica, C. asiatica, and A. cathartica reduced blood glucose level by 78.95 %, 74.50 %, and 70.19 %, respectively, compared to the standard drug metformin, which reduced blood glucose levels by 85.84 %. A. zeylanica at 400 mg/kg BW dose and metformin demonstrated statistically similar and significant blood glucose level reduction (p < 0.001). Additionally, therapeutic doses of A. zeylanica leaf extract exhibited low cytotoxicity (cell survival rate >89 %), highlighting its potential as a safe and effective source of antidiabetic agent.